Shaking Table Test Study on the Earthquake Behavior of High-Speed Railway Bridge Pier with Rounded Rectangular Cross Section. (6th September 2022) - Kang, Xin; Zuo, Yongjian; Zeng, Leqiao; Peng, Linna; Wang, Qiliang; Wang, Xiaoxiang; Deng, Libin; Hu, Jia; Li, Zhuo; Li, Likun
Abstract : Rounded rectangular cross section piers were widely used for high-speed railway (HSR) bridges in China. However, the performance of such piers under seismic scenarios has not been well studied. To study the earthquake behavior and damage of rounded rectangular cross section piers under different intensities of earthquake excitation, nine scaled pier specimens were constructed and tested on the shaking table. Experimental results show that the specimen remains elastic (no or slight damaged) for all experimental earthquake scenarios (from 0.45 g to 0.96 g). Finite element (FE) models were developed and validated by the experimental results. Using this FE model, the damage levels of these specimens under severe earthquake excitations (from 1.05 g to 1.95 g) were quantified. Numerical results show that the specimen in transverse direction shows no or slight damage, while repairable damage can be seen in longitudinal direction as the earthquake intensity increases from 1.05 g to 1.65 g. Repairable and unrepairable damage can be seen in transverse and longitudinal direction, respectively, as the earthquake intensity increases to 1.95 g. Researchers can make good use of these findings for better earthquake design or protection of this type of HSR piers in the future.